Celiac disease prevalence in epileptic children from Serbia - Djurić, Zlatko; Nagorni, Aleksandar; Jocić-Jakubi, Bosa; Dimić, Milena; Novak, Martin; Milićević, Radovan; Radenković, Goran (The Turkish Journal of Pediatrics, 2012)
Celiac disease (CD) is a genetically determined autoimmune enteropathy, induced by gluten ingestion. To date, different prevalences of CD in children with epilepsy have been reported. The aim of this study was to determine CD prevalence in our patients with epilepsy, using anti-tissue transglutaminase (tTG) antibodies as a screening test. One hundred twenty-five children (72 girls, 53 boys; age range: 2-18 years, mean age: 10.51 +/- 3.53) with idiopathic epilepsy from South East Serbia were tested for immunoglobulin (IgA) tTG antibodies. All positive patients were offered endoscopic small bowel biopsy. Biopsies were examined histopathologically in order to confirm the CD diagnosis. The control group consisted of 150 healthy children. Three patients with epilepsy were positive for IgA tTG antibodies. In all of them, small bowel biopsy was performed, and only one was proven to have CD by histopathology (Marsh IIIa grade). The prevalence of biopsy-proven CD in children with epilepsy was not significantly higher in the study group compared to controls (0.8% vs.0.6%, p > 0.05). The results of this study indicate that children with idiopathic epilepsy from our region should not be routinely tested for CD.